Inclusão universitária no século XXI dilemas atuais - Ciantelli, Ana Paula Camilo (Editora Oficina Universitária, 2023)
What obstacles are present in political and academic discourses in Higher Education in contemporary times? What theoretical-methodological discourses have mobilized changes in university institutional policies? What are we advancing? What needs to change for universities to be more inclusive? What paths to take to ensure that human plurality constitutes the ways of existing of different bodies that inhabit and/or transit in the spaces of the University? What plans and actions are needed to transform obstacles into facilitators for the promotion of inclusive cultures, policies and practices in Higher Education? Questions like these and so many others were captured by a constant becoming by the commitment of those who ventured to share perceptions embodied in the multiplicity of understandings that mobilized the title of this work, "University inclusion in the 21st century: current dilemmas".